2010
DOI: 10.2478/s11536-010-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Anal HPV infection in Slovenian men who have sex with men

Abstract: AbstractAnal human papillomavirus (HPV) infection commonly affects men who have sex with men (MSM) and is associated with the development of anal cancer, with the highest prevalence in MSM who are positive for human immunodeficiency virus (HIV). The purpose of this study was to determine the prevalence of anal HPV infection and genotype distribution in Slovenian MSM and its correlation with behavioral patterns in order to predict the possible impact of quadrivalent HPV vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…In addition, "poppers" suppress the function of natural killer cells, which further increases susceptibility to infection [19]. In general, our findings are similar to what has previously been observed for anal ␣-PV infection by us and others (reviewed in [9]), indicating that ␤-PVs may also be transmitted sexually. This assumption is further supported by a recent HPV type distribution studies that identified a wide variety of ␤-PV types in male external genitalia [20,21], of which the majority was also detected in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, "poppers" suppress the function of natural killer cells, which further increases susceptibility to infection [19]. In general, our findings are similar to what has previously been observed for anal ␣-PV infection by us and others (reviewed in [9]), indicating that ␤-PVs may also be transmitted sexually. This assumption is further supported by a recent HPV type distribution studies that identified a wide variety of ␤-PV types in male external genitalia [20,21], of which the majority was also detected in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The study has been carried out in accordance with the code of Ethics of the World Medical Association (Declaration of Helsinki) and has been approved by the National Medical Ethics Committee of the Republic of Slovenia (consent number: 131/06/07). Of 135 subjects, 123 originated from our previous study investigating the prevalence of ␣-PV in the anal region [9] and 12 were newly enrolled. The study subjects aged from 17 to 81 years (median age = 31 years) and 23/135 (17.0%) were HIV-1 positive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of total DNA (n = 458), extracted from 249 swabs of the anal canal (226 initial and 23 follow-up samples), 94 cervical cancer formalin-fixed paraffinembedded (FFPE) tissue samples, 21 genital warts (11 swabs and 10 biopsies) from different anatomical sites [foreskin (n = 4), scrotum (n = 2), penile glans (n = 2), perianal area (n = 4) and pubis (n = 9)], and 94 oral swabs collected during routine paternity testing, were obtained from the archival collection of samples of the Instituto de Biología Molecular y Celular de Rosario (Rosario, Argentina) and the Institute of Microbiology and Immunology, Faculty of Medicine, University of Ljubljana (Ljubljana, Slovenia). Before subsequent analyses, all samples were collected, processed, and stored at − 80°C, as described previously [11,27,[29][30][31][32]. The adequacy of samples for downstream analyses was determined by PCR amplification of the human beta-globin gene, as previously described [33].…”
Section: Patients' Data Sample Collection and Processingmentioning
confidence: 99%
“…Alpha-PV infections of the anal canal have frequently been detected in human immunodeficiency virus (HIV-1)-infected men who have sex with men (MSM) [5,6]. Moreover, HIV-1-positive MSM have approximately 60 times higher risk of developing anal cancer than the general population [7,8], and also show higher risk with respect to men who have sex with women (MSW) [9], women [10], and HIV-1-negative MSM [11], but in lower proportions.…”
Section: Introductionmentioning
confidence: 99%